DEVELOPMENT OF LEG STRENGTH AT YOUNG PLAYERS OF HANDBALL CLUB NOVI PAZAR - Fahrudin Mavrić; Vladan Milić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
We have been developing explosive leg strength during the whole year. The most attention is paid at preparation period. At the first stage of that period, we develop general explosive leg strength. After reaching motor efficiency of explosive leg strength, in order to prevent losing it fast, we have to keep it in progress during the main period. We have carried it out mostly on conditional athletic trainings, at least on weekly basis and frequently on trainings plan- ned for technical and tactical preparation, in intervals of 10 - 15 minutes, final stage of training. I have undertaken experimental development of leg strength in the preparation period, half- season (January - February) with the cadets of handball club Novi Pa- zar, aged 14 - 16, competitors in La vita league and the winners at the end of season 2006/07. The team convincingly won the first place with thirteen wins and one tie score, after 28 trainings with compulsory exercises for the explosive leg strength